ANALISIS AKTIVITAS BELAJAR SISWA PADA PEMBELAJARAN GEOGRAFI MATERI KONDISI WILAYAH DAN POSISI STRATEGIS INDONESIA SEBAGAI POROS MARITIM DUNIA DI SMA NEGERI 5 KOTA PADANG - handrian hidayat; Rahmanelli Rahmanelli (JURUSAN GEOGRAFI FIS UNP, 2020)
This article was written to analyze student learning activities, constraints faced by teachers and efforts made by teachers in developing student learning activities in learning geography of regional conditions and Indonesia's strategic position as the world's maritime axis. This type of research uses a descriptive method with a quantitative approach. The population in this study were all students of class XI IPS. Sampling using Purposive Sampling technique with selected sample results is class XI IPS 2. The results of this study indicate that student learning activities in the matter of regional conditions and Indonesia's strategic position as the world's maritime axis in SMA Negeri 5 Padang is low. While the constraints faced by teachers for basic learning activities are the lack of textbooks and for the constraints on advanced learning activities is the difficulty of controlling students when using a smartphone.